El crecimiento económico y la incidencia en la pobreza del departamento de Ancash: 2001-2015 - Alvarez Gavidia, Juan Antonio (2016)
This paper examined whether economic growth reduced poverty levels in the department of Ancash during the period 2001-2015. Considering the hypothesis that economic growth would have favored the reduction of poverty levels, aggregate trends analysis, arc poverty elasticity, econometric log-log growth poverty elasticity, and the calculation of pro-poor growth , Reporting evidence that is consistent. From the results of the elasticities, it was concluded that growth had a positive impact on poverty reduction by improving people's living conditions, resulting in pro-poor growth, benefiting the extreme poor more than the total poor. In addition, it was concluded that growth has had a greater impact on the poverty reduction of the provinces of the sierra than on the coast, despite the fact that the poorest provinces are still in the high Andean rural areas, due to the dispersion Geographical area.